Next-Generation Active-Clamp Forward-Flyback Converter With Integrated Planar Transformer for 4 kW LDC - Gyeong-Hyun Kwon; Dong-In Lee; Seong-Wook Jeong; Han-Shin Youn (IEEE Access)
This paper proposes a single-module Active-Clamp Forward-Flyback (ACFF) converter for the next-generation low-voltage DC-DC converter (LDC) ensuring 4kW output power. The proposed converter employs an integrated planar transformer for applications requiring wide input voltage and high output current. Previously, to meet the 4kW output specification, two 2kW LDC single modules were connected in series-parallel, resulting in a total of four cores functioning as transformers and output inductors. The core of the proposed converter consists of one core functioning as a transformer and two cores functioning as output inductors, resulting in higher power density and cost competitiveness compared to the conventional 4kW LDC modules. Additionally, integrating the cores from four to three offers the advantage of reduced magnetic core losses. In conclusion, the proposed converter is suitable for high-power LDC applications exceeding 3kW.